Characterization on ferroelectric scandium-doped aluminum nitride for memory applications - Wang, Zichu (Nanyang Technological University, 2023)
Ferroelectric memory is one of the promising candidates to replace FLASH as a new generation of non-volatile memories (NVM), with the advantages of low power consumption, thigh writing and erasing speed and large endurance. With the discovery of ferroelectricity in scandium doped aluminum nitride >100 μC/cm2 , it is expected to be of many advantages over ferroelectric memories. In this thesis, we report the tendency of ferroelectric properties in AlScN varying with residual stress and thickness. Ferroelectricity in a 10nm Al0.7Sc0.3N thin film is observed and reported in this thesis as well. Capacitors with a Mo/Al0.7Sc0.3N/Al structure where thickness of Al0.7Sc0.3N is 50nm exhibit high endurance up to 10 6 switching cycles, indicating broad application prospects in ferroelectric storage.